Sytematic Literature Review: Kelayakan Media Pembelajaran Mobile Learning Sebagai Penunjang Pembelajaran MIPA Di Indonesia - Muhammad Maulana Husaen; Hadma Yuliani (Lembaga Bale Literasi, 2023)
This research is a systematic review of mobile learning media as a support for MIPA (mathematics and natural sciences) learning in Indonesia. In this study, an exploration of related journals was carried out, as well as an analysis of the suitability and effectiveness of using mobile learning in MIPA learning in Indonesia. The method used is a systematic literature review (SLR), with planning, implementation, and reporting stages. In the implementation phase, a journal search is carried out using Google Scholar with the help of the Publish or Perish 8 application, with the specified inclusion and exclusion criteria. The data obtained was analyzed to assess the quality of the journal and extract information according to the research topic. The results of the analysis show that mobile learning media has feasibility in MIPA learning in Indonesia by increasing the accessibility, flexibility, interactivity and involvement of students. The advantages of this medium including increased motivation, interactive learning experiences, and the ability to monitor learning progress. However, it is necessary to pay attention to deficiencies such as limited internet access and lack of content development in accordance with the curriculum. This research provides an in-depth understanding of mobile learning media in the context of MIPA learning in Indonesia and can be used as a basis for better development and implementation.